Molecular and neuronal plasticity mechanisms in the amygdala-prefrontal cortical circuit: implications for opiate addiction memory formation - Rosen, Laura G.; Sun, Ninglei; Rushlow, Walter; Laviolette, Steven R. (Frontiers in Neuroscience, 2015)
The persistence of associative memories linked to the rewarding properties of drugs of abuse is a core underlying feature of the addiction process. Opiate class drugs in particular, possess potent euphorigenic effects which, when linked to environmental cues, can produce drug-related ‘trigger’ memories that may persist for lengthy periods of time, even during abstinence, in both humans and other animals. Furthermore, the transitional switch from the drug-naïve, non-dependent state to states of dependence and withdrawal, represents a critical boundary between distinct neuronal and molecular substrates associated with opiate-reward memory formation. Identifying the functional molecular and neuronal mechanisms related to the acquisition, consolidation, recall and extinction phases of opiate-related reward memories is critical for understanding, and potentially reversing, addiction-related memory plasticity characteristic of compulsive drug-seeking behaviors. The mammalian prefrontal cortex (PFC) and basolateral nucleus of the amygdala (BLA) share important functional and anatomical connections that are involved importantly in the processing of associative memories linked to drug reward. In addition, both regions share interconnections with the mesolimbic pathway’s ventral tegmental area (VTA) and nucleus accumbens (NAc) and can modulate dopamine (DA) transmission and neuronal activity associated with drug-related DAergic signaling dynamics. In this review, we will summarize research from both human and animal modelling studies highlighting the importance of neuronal and molecular plasticity mechanisms within this circuitry during critical phases of opiate addiction-related learning and memory processing. Specifically, we will focus on two molecular signaling pathways known to be involved in both drug-related neuroadaptations and in memory-related plasticity mechanisms; the extracellular-signal-regulated kinase system (ERK) and the Ca2+/calmodulin-dependent protein kinases (CaMK). Evidence will be reviewed that points to the importance of critical molecular memory switches within the mammalian brain that might mediate the neuropathological adaptations resulting from chronic opiate exposure, dependence and withdrawal.